De Novo 17q24.2–q24.3 microdeletion presenting with generalized hypertrichosis terminalis, gingival fibromatous hyperplasia, and distinctive facial features. (31st May 2015) - Afifi, Hanan H.; Fukai, Ryoko; Miyake, Noriko; Gamal el Din, Amina A.; Eid, Maha M.; Eid, Ola M.; Thomas, Manal M.; El‐Badry, Tarek H.; Tosson, Angie M. S.; Abdel‐Salam, Ghada M. H.; Matsumoto, Naomichi
<x xml:space="preserve">Abstract</x> Generalized hypertrichosis is a feature of several genetic disorders, and the nosology of these entities is still provisional. Recent studies have implicated chromosome 17q24.2–q24.3 microdeletion and the reciprocal microduplication in a very rare form of congenital generalized hypertrichosis terminalis (CGHT) with or without gingival hyperplasia. Here, we report on a 5‐year‐old Egyptian girl born to consanguineous parents. The girl presented with CGHT and gingival hyperplasia for whom we performed detailed clinical, pathological, and molecular studies. The girl had coarse facies characterized by bilateral epicanthic folds, thick and abundant eyelashes, a broad nose, full cheeks, and lips that constituted the distinctive facial features for this syndrome. Biopsy of the gingiva showed epithelial marked acanthosis and hyperkeratosis with hyperplastic thick collagen bundles and dense fibrosis in the underlying tissues. Array analysis indicated a 17q24.2–q24.3 chromosomal microdeletion. We validated this microdeletion by real‐time quantitative PCR and confirmed a perfect co‐segregation of the disease phenotype within the family. In summary, this study indicates that 17q24.2–q24.3 microdeletion caused CGHT with gingival hyperplasia and distinctive facies, which should be differentiated from the autosomal recessive type that lacks the distinctive facies. © 2015 Wiley Periodicals, Inc.